The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1037/a0027332
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion, avoidance, and daily negative affect among couples coping with prostate cancer: A dyadic investigation.

Abstract: In the present study we examined how husbands' and wives' intrusive thoughts of prostate cancer (i.e., thinking about it when not meaning to) and avoidance (i.e., efforts to not think about cancer) related to their own and each other's average negative affect over a subsequent 14-day period. We examined whether congruence or similarity in intrusion about illness, but not avoidance, would be associated with less negative affect as this response to cancer could potentially facilitate adjustment. Fifty-nine husba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…The interaction of individual coping efforts has been the focus of the coping congruence approach to dyadic coping, and although only one empirical study was found to have used this specific theoretical model in the past decade, researchers should not overlook the importance of the interaction between the two partners' individual coping efforts. It is a basic premise of a dyadic approach to stress and coping that the match or lack thereof between partners will influence not only their own coping outcomes but also the health and strength of the relationship (Fagundes, Berg, & Wiebe, ). Employing qualitative methods that capture partners' perceptions of their own and their partners' coping processes (and their overlap or conflict) and multilevel modeling procedures in future studies promises more in‐depth and more precise modeling of these coping interdependencies.…”
Section: Dyadic Stress and Coping: An Ecological Intra‐ And Interpersmentioning
confidence: 99%
“…The interaction of individual coping efforts has been the focus of the coping congruence approach to dyadic coping, and although only one empirical study was found to have used this specific theoretical model in the past decade, researchers should not overlook the importance of the interaction between the two partners' individual coping efforts. It is a basic premise of a dyadic approach to stress and coping that the match or lack thereof between partners will influence not only their own coping outcomes but also the health and strength of the relationship (Fagundes, Berg, & Wiebe, ). Employing qualitative methods that capture partners' perceptions of their own and their partners' coping processes (and their overlap or conflict) and multilevel modeling procedures in future studies promises more in‐depth and more precise modeling of these coping interdependencies.…”
Section: Dyadic Stress and Coping: An Ecological Intra‐ And Interpersmentioning
confidence: 99%
“…Adopting a dyadic paradigm requires adopting a dyadic analytic approach. Indeed, recent studies have successfully used dyadic analytic approaches to understand relationship support and coping in cancer patients and their partners (e.g., Berg et al, 2008; Fagundes, Berg, & Wiebe, 2012). …”
Section: The Dyadic Stress and Coping Paradigmmentioning
confidence: 99%
“…That is, couples experience the effects of one partner’s illness differently in their relationships (Berg et al, 2008; Checton, Greene, Magsamen-Conrad, & Venetis,2012; Fagundes, Berg, & Wiebe, 2012; Merz et al, 2011). Differential illness experiences between patients and partners are worth exploring to develop strategies for supporting couples, especially with respect to variables over which they have control (e.g., communication perceptions, patterns, and practices) in comparison to those they cannot control (e.g., the chronic illness itself).…”
Section: Couples’ Cancer Managementmentioning
confidence: 99%
“…That is, patients’ and partners’ dyadic appraisals of discrete moments and day-to-day discourses that are inherent to coping with cancer are salient in terms of the couple’s adjustment (cancer management). Recent studies have explored dyadic coping appraisals (e.g., collaborative, concordant) and outcomes (e.g., quality of life, psychological distress, management) among patients and partners managing different types of cancers including breast cancer (Feldman & Broussard, 2006; Kayser, Sormanti, & Strainchamps, 1999; Kayser, Watson, & Andrade, 2007), head and neck cancers (Foxwell & Scott, 2011), and prostate cancer (e.g., Berg et al, 2008; Fagundes et al, 2012; Fergus, 2011). For example, among prostate cancer patients and their partners, Merz et al (2011) found that concordant dyads (i.e., coping appraisal agreement on prostate cancer characteristics) reported better individual health-related quality of life compared to non-concordant dyads (i.e., coping appraisal disagreement).…”
Section: Dcmmentioning
confidence: 99%